2021
DOI: 10.26822/iejee.2021.228
|View full text |Cite
|
Sign up to set email alerts
|

Some Predictors of Perceived Support and Proximity in Students during COVID-19 Distance Learning

Abstract: Due to the COVID-19 pandemic, distance learning and social isolation have dramatically changed the social and learning experiences of adolescents. Given that social isolation can adversely affect students' psychosocial well-being, our study examined the extent to which ICT competences, resilience, and individual types of contact with teachers and classmates contribute to the psychosocial well-being of lower secondary school students (N = 1,813) over an extended period of distance learning. The questionnaires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…However, research shows that high-quality relationships between students themselves and between students and teachers are moderate predictors of student learning achievement (e.g., meta-analysis by Hattie, 2009) and that they increase students' psychosocial well-being, e.g., with less peer bullying (Košir et al, 2018). Pečjak et al (2021) found that teachers attended to students' psychosocial wellbeing either by organizing more collaborative learning in the e-classroom (e.g. by videoconferences) or by organizing additional contact with students outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…However, research shows that high-quality relationships between students themselves and between students and teachers are moderate predictors of student learning achievement (e.g., meta-analysis by Hattie, 2009) and that they increase students' psychosocial well-being, e.g., with less peer bullying (Košir et al, 2018). Pečjak et al (2021) found that teachers attended to students' psychosocial wellbeing either by organizing more collaborative learning in the e-classroom (e.g. by videoconferences) or by organizing additional contact with students outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Dvorsky et al (2021) suggest that during the COVID-19 crisis, intrinsic curiosity and a positive mindset may be especially essential for developing resilience. Pecjak et al (2021) hold that because to the COVID-19 epidemic, adolescents' social and learning experiences have been drastically altered by distant learning and social isolation, thereby affecting their resiliency. Their research discovered a link between resilience and adolescents' psychological wellbeing.…”
Section: Adolescent Resiliencementioning
confidence: 99%
“…The COVID-19 pandemic has drastically changed the lives of children and adolescents around the world. Much of life has come to a standstill, including the closing of educational institutions, the transition to distance learning, and the requirement to reduce interpersonal contact 'i.e., maintain social distance' (Pečjak et al, 2021). Social isolation, such as the children's inability to visit their friends or relatives frequently, affected their social and emotional behaviors (Xiang et al, 2022).…”
mentioning
confidence: 99%